A clinico-demographic profile of 110 male patients with genital ulcer(s) - Kumar, Piyush; Mondal, Avijit; Chowdhury, Satyendra Nath; Das, Nilay Kanti; Datta, Pijush Kanti; Gharami, Ramesh Chandra (Journal of Pakistan Association of Dermatologists, 2018)
Objective To assess the magnitude of male genital ulcer (MGU) and its clinico-demographic profile in patients attending dermatology OPD and STI clinic of a tertiary care hospital in the eastern part of India. Â Methods The study was institution-based cross-sectional descriptive study conducted over a period of one year. All the male patients presenting to Dermatology OPD and STI clinic with complaints of genital lesions were screened for genital ulcer/s. Those having genital ulcer and giving consent for participating in the study were included in the study. At the end of study period, data were analyzed. Â Results 110 patients with MGU among 22,528 male patients attending Dermatology OPD and STI clinic were included in study and relative prevalence rate was calculated as 4.88 per 1000. Non-sexually transmitted ulcers (non-STU) [65.5%] were leading cause of MGU. Among sexually transmitted ulcers (STU), genital herpes was the most common disease. Dermatitis-related ulcer, scabies related ulcer, and Zoonâ€™s balanitis (plasma cell balanitis) were most common non-STU. Positive history of sexual exposure was found in around 53.2%, 97.4% and 22.2% of MGU, STU and non-STU, respectively. Commercial sex workers were the major sex partner in both STU and non-STU groups. Â Conclusion Non-sexually transmitted ulcers were more common than sexually transmitted ulcers. History of sexual exposure was seen in both STU, and non-STU. Hence, history of sexual exposure should not bias clinician towards making a diagnosis of STU. Â